Survey of Housing Typologies and Infrastructural Problems in Public Housing Estate in Awka, Anambara State - Iwuchukwu Okafor (IIARD INTERNATIONAL JOURNAL OF GEOGRAPHY AND ENVIRONMENTAL MANAGEMENT, 2026)
A survey of public housing typologies demand needs and supply in Awka, has shown persistent increase since the creation of the state in 1991. Increase in commercial, industrial and government activities have resulted in the high demand for dwelling units. In most urban centres, like Awka and Ontisha, demand outstrips supply, hence increasing pressure on rents and affordability rates. With the increase in cost of building materials. It was suggested that localization of sourcing of local materials for building construction would help reduce scarcity at the same time address persistent rent increases. Government is further called to deregulate the housing business so that private and cooperate individuals would become secured to participate in the promising of housing units in the area.